Fabrication, optimisation and evaluation of cisplatin-loaded nanostructured carriers for improved urothelium permeability for intravesical administration. (18th August 2021) - Chen, Ting-Yu; Tai, Yu-Yao; Chang, Li-Ching; Wu, Pao-Chu
Abstract: Aim: To design microemulsions as carriers to improve cisplatin permeation capability for intravesical administration. Method: The response surface methodology with factorial design was used to investigate and optimise the influence of the compositions e.g. capryol 90 and 5-pentanediol/transcutol mixture on the permeation accumulation amount and tissue deposition amount of cisplatin-loaded microemulsions. The in vitro permeation study and in vivo intravesical test were conducted to prove the effect of microemulsions. Results: The droplet size and the viscosity of all drug-loaded formulations ranged 235.8–309.3 nm and 550.8–861.7 cps, respectively. The permeation accumulation amounts significantly increased about 26-fold, by used microemulsion as carriers. In vivo study, the cisplatin deposition amount in bladder tissue significantly increased 4.1-fold ( p < 0.05) and the penetration depth increased from 60 μm up 120 μm. The nanocarrier showed considerable thermodynamic stability. Conclusion: The designed nanocarrier was considered to be a promising delivery system for cisplatin intravesical administration.